Old English Simile of Equality: The Highest Degree of Similarity - Oleniak, Mariana (Research in Language, 2018)
This paper aims to provide an account of Old English similes of equality marked by the superlative degree of the adjective gelic. It deals with the structure and semantics of similes marked by the (ge)/(on)licost component, which, unlike in Modern English, being subjected to gradation, can show the highest degree of similarity between referents. The article presents the criteria for structural classification of the simile in question describing two major structural types, that employ nouns in the dative or nominative case, as well as its semantic interpretation from macro and micro levels of perspective. The paper examines every simile with the (ge)/(on)licost component found in Old English manuscripts belonging to various textual genres.